How not to Write like Cicero: Pridie quam in exilium iret oratio - Corbeill, Anthony (Ciceroniana On Line, 2020)
This article examines the pseudo-Ciceronian Pridie quam in exilium iret oratio, a short work that appears at the head of our best witnesses for Cicero’s genuine post reditum speeches. Supplementing the work of previous scholars, I catalogue Ciceronian and non-Ciceronian works to which the author seems to refer and compare that list to those texts that were thought to be taught in the schools. The mismatch between the two lists leads to a discussion of other non-Ciceronian idiosyncrasies: prose rhythm; multiple addressees; the anonymity of Clodius; the references to Cicero in the third person; the use of hyperbaton. I close by suggesting that this exercise shows a student willfully, even perversely, creating an independent oration in reaction to the restrictions of declamatory practice in the school.